Identifying predictive clinical characteristics of the treatment efficacy of mirtazapine monotherapy for major depressive disorder - Tsutsumi T; Sugawara H; Ito R; Asano M; Shimizu S; Ishigooka J; Nishimura K (Neuropsychiatric Disease and Treatment, 2016)
Takahiro Tsutsumi,1 Hiroko Sugawara,1,2 Ryoko Ito,1 Mizuho Asano,1 Satoru Shimizu,3 Jun Ishigooka,1 Katsuji Nishimura1 1Department of Psychiatry, 2Support Center for Women Health Care Professionals and Research, 3Department of Research, Medical Research Institute, Tokyo Women’s Medical University, Tokyo, Japan Background: Mirtazapine, which is classified as a noradrenergic and specific serotonergic antidepressant, is widely prescribed for the treatment of major depressive disorder. The potential predictive factors of the efficacy of mirtazapine and the tolerability based on the incidence of oversedation and jitteriness/anxiety syndrome were evaluated. Patients and methods: Patients with major depressive disorder were retrospectively investigated. Study subjects comprised 68 patients with depression who received mirtazapine as an initial antidepressant at the Department of Psychiatry of the Tokyo Women’s Medical University Hospital from September 2009 to March 2013. The efficacy of mirtazapine monotherapy was evaluated based on the Clinical Global Impression Improvement score. Clinical characteristics were compared between remission and nonremission groups to determine the factors predicting the efficacy. Moreover, discontinuation rates due to adverse effects, including oversedation and jitteriness/anxiety syndrome, were examined, and the effects of confounding factors were evaluated. Results: The remission rate of mirtazapine monotherapy was 36.8% among the 68 enrolled subjects. The mean final doses in the remission and nonremission groups were 27.6±13.5 mg and 26.0±14.1 mg, respectively, and there was no significant difference between them. Multiple logistic analyses revealed that the absence of guilt (odds ratio [OR] =0.15; 95% CI [1.66–37.24], P=0.006) and the presence of psychomotor retardation (OR =4.30; 95% CI [1.30–16.60], P=0.016) were significantly related to the efficacy of mirtazapine monotherapy. The discontinuation rates due to oversedation and jitteriness/anxiety syndrome were 13.2% and 11.8%, respectively. Age did not differ significantly between patients with or without oversedation or jitteriness/anxiety syndrome (P=0.078 and P=0.579, respectively). Conclusion: The absence of guilt and the presence of psychomotor retardation may predict the efficacy of mirtazapine, and mirtazapine may be tolerable for all ages. Keywords: feelings of guilt, psychomotor retardation, oversedation, jitteriness, anxiety syndrome